ナンキョク リュツォ・ホルムワン ラングボブデ チイキ ノ チシツ - 石川, 輝海; イシカワ, テルミ; ISHIKAWA, Terumi (国立極地研究所, 1974)
P(論文) The rocks exposed in Langhovde, Liitzow-Holm Bay, East Antarctica, are chiefly metamorphic and granitic, with less extensive glacial deposits and beach sediments. Metamorphic rocks consist of metabasite, pyroxene gneiss, hornblende gneiss, garnet-biotite gneiss, porphyroblastic gneiss, garnet gneiss and garnetbearing granitic gneiss. These rocks generally show gentle angle foliation striking northeast and may be Precambrian or possibly Early Paleozoic in age. The metamorphic rocks of Langhovde have a prominent compositional layering or foliation, denned by alternation of quartz-feldspathic, quartzitic, garnetbiotitic or amphibolitic layers of all scales from a fraction of a centimeter to several tens of meters. Foliation is weak in pyroxene gneiss and hornblende gneiss. In the garnet-biotite gneiss and porphyroblastic gneiss, foliation is accentuated by the parallel arrengement of biotite, garnet, feldspars and quartz. The northern part of Langhovde is marked with fold structures, represented by anticlines with an axis of N45°W and synclines with an axis of E-W. In the southern part is found a monoclinal structure striking NE and dipping to the west. Granitic rock is microcline granite, which occurs in the vicinity of Hukuro Cove. The rock is slightly gneissic, pink-colored, and coarse-grained, and it consists mainly of quartz, perthite or perthitic microcline, and biotite, with small amounts of plagioclase and garnet. Glacial deposits are distributed all over the ice-free area, and particularly thick along the boundary between the continental ice and the ice-free area. Immediately overlying the basement is a glacial deposit composed of gneissose rock boulders and cobbles. The boulders are typically rounded and seem to be similar in composition to the underlying basement gneiss. Beach gravel and sand form a terrace along the shore of the inlet and include fossil shells (Adamussium colbecki and Laternula elliptica). ^<14>C age of them shows 3840 ±90 years B.P. departmental bulletin paper